Post-traumatic stress disorder among Syrian refugees in Turkey: A cross-sectional study - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2015)
Objective. Refugees have had major challenges to meet their health care needs throughout history especially in war zones and natural disaster times. The health care needs of Syrian refugees have been becoming an increasingly important issue. We aimed to examine the prevalence of post-traumatic stress disorder (PTSD) and explore its relation with various socioeconomic variables among Syrian refugees, who sought asylum in Turkey. Methods. This cross-sectional study was conducted in a tent city. Sample size calculation yielded 352 and the participants of the study were determined randomly. Experienced and native Arabic speaking, psychiatrist evaluated the participants. Results. The frequency of PTSD was 33.5%. Through the binary logistic regression analysis, we calculated that the probability of having PTSD among Syrian refugees in our sample was 71%, if they had the following features: with female gender; being diagnosed with psychiatric disorder in the past; having a family history of psychiatric disorder; and experiencing 2 or more traumas. Conclusions. The findings of our study suggest that PTSD among Syrian refugees in Turkey might be an important mental health issue in refugee camps especially among female refugees, who were exposed to 2 or more traumatic events and had a personal or family history of psychiatric disorder.
Keywords: Post-traumatic stress disorder; Syrian refugees; tent city; MENTAL-HEALTH; ASYLUM SEEKERS; TRAUMA; SYMPTOMS; WAR